Formulation and Evaluation of Ethyl Cellulose Coated Microcapsules of Glibenclamide for Controlled Release - Dwarakanadha Reddy, P.; Surya Prakash, A.; Shafi, Shaik; Usha Sree, R.; Thippa Reddy, T.; Swarnalatha, D.; Prasanthi, S. (Asian Journal of Chemistry, 2014)
Microencapsulation has been widely employed in the design of controlled release dosage forms. Glibenclamide has short biological half-life of 4-6 h and is eliminated rapidly. Therefore control release products are needed for glibenclamide to prolong its duration of action and to improve patience compliance. In the present investigation, studies were carried out on microencapsulation of glibenclamide by ethyl cellulose as a polymer with an objective of developing glibenclamide micro capsules for oral controlled release because this drug require to control release formulation for better control of hypoglycemia and to enhance their therapeutic efficacy and for improved patient compliance. Microcapsules were successfully prepared by an emulsification solvent evaporation method. All the microcapsules prepared were evaluated for size and size distribution, drug content of microcapsules, microencapsulation efficiency, wall thickness, dissolution rate kinetics and mechanism. The yields were varies from 95-98 % and encapsulation efficacy is maximum. The FTIR studies used to confirmed the interaction between drug and polymer. The SEM photograph of microcapsules confirmed good spheres and smooth surface.